Matricryptins Network with Matricellular Receptors at the Surface of Endothelial and Tumor Cells - Ricard-Blum, Sylvie; Vallet, Sylvain D. (Frontiers in Pharmacology, 2016)
The extracellular matrix is a source of bioactive fragments called matricryptins or matrikines resulting from the proteolytic cleavage of extracellular proteins (e.g. collagens, elastin and laminins) and proteoglycans (e.g. perlecan). Matrix metalloproteinases (MMPs), cathepsins and bone-morphogenetic protein-1 release fragments, which regulate physiopathological processes including tumor growth, metastasis and angiogenesis, a pre-requisite for tumor growth. A number of matricryptins, and/or synthetic peptides derived from them, are currently investigated as potential anti-cancer drugs both in vitro and in animal models. Modifications aiming at improving their efficiency and their delivery to their target cells are studied. However their use as drugs is not straightforward. The biological activities of these fragments are mediated by several receptor families. Several matricryptins may bind to the same matricellular receptor, and a single matricryptin may bind to two different receptors belonging or not to the same family such as integrins and growth factor receptors. Furthermore some matricryptins interact with each other, integrins and growth factor receptors crosstalk and a signaling pathway may be regulated by several matricryptins. This forms an intricate 3D interaction network at the surface of tumor and endothelial cells, which is tightly associated with other cell-surface associated molecules such as heparan sulfate, caveolin and nucleolin. Deciphering the molecular mechanisms underlying the behavior of this network is required in order to optimize the development of matricryptins as anti-cancer agents.